2008
DOI: 10.2967/jnumed.108.050849
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptor PET Reveals the Psychobiologic Correlates of Reward Processing

Abstract: Little is known about the neurobiologic correlates of human personality. On the basis of the key role of the central opioidergic system in addiction and substance abuse, we investigated the relationship between certain personality traits that are supposed to be relevant in addiction and the opioid receptor status in healthy subjects. Methods: We investigated 23 healthy male volunteers who were extensively clinically tested to exclude substance abuse. All of the subjects underwent 1 PET scan with the subtype-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…For example, the ventral striatum is also an important site of opioidergic neurotransmission, and conse- quently, the link between placebo analgesia and ventral striatum might be accounted for partly by interindividual differences in opioidergic function. Schreckenberger et al (2008) showed that opioid receptor binding potentials in the ventral striatum correlate with the trait of reward dependence. In contrast, they did not find a relationship between opioids and novelty seeking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ventral striatum is also an important site of opioidergic neurotransmission, and conse- quently, the link between placebo analgesia and ventral striatum might be accounted for partly by interindividual differences in opioidergic function. Schreckenberger et al (2008) showed that opioid receptor binding potentials in the ventral striatum correlate with the trait of reward dependence. In contrast, they did not find a relationship between opioids and novelty seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, dysregulation or disequilibrium of brain neurotransmitters have repeatedly been linked to mental diseases. Therefore, a better understanding of neurotransmitter systems and their involvement in personality and behavior may subsequently pave the way for improved treatment strategies for a multitude of neuropsychiatric disorders.Though temperament research has mainly implicated central monoaminergic systems, mounting evidence points toward a more complex neurotransmitter interplay to account for the variation in human personality (5,6,8). Glutamate is the main excitatory neurotransmitter in the brain and is involved in numerous aspects of behavior and cognition.…”
mentioning
confidence: 99%
“…Though temperament research has mainly implicated central monoaminergic systems, mounting evidence points toward a more complex neurotransmitter interplay to account for the variation in human personality (5,6,8). Glutamate is the main excitatory neurotransmitter in the brain and is involved in numerous aspects of behavior and cognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As well, another important line of research is the opioid system and its relation to reward behaviour. Schreckenberger et al [34], using the opioidergic radioligand 18 F-fluoroethyl-diprenorphine, found a correlation between scores of reward dependence and binding potential in the ventral striatum and nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%